2017
DOI: 10.1177/1474515117715842
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support and self-care in patients hospitalized with heart failure

Abstract: This study supports the premise that heart failure rehospitalizations are related to inadequate self-care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 43 publications
3
56
0
3
Order By: Relevance
“…In addition, we found the mean scores of depressive symptoms for patients in both groups were higher than the cut-off values of Self-care is considered the cornerstone of HF treatment and the prevention of rehospitalisation (Chamberlain, 2017;Navidian et al, 2017;Shao et al, 2010;Xie et al, 2016). Our results support the findings; HF patients with lower self-care scores were likely to be readmitted to the hospital.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In addition, we found the mean scores of depressive symptoms for patients in both groups were higher than the cut-off values of Self-care is considered the cornerstone of HF treatment and the prevention of rehospitalisation (Chamberlain, 2017;Navidian et al, 2017;Shao et al, 2010;Xie et al, 2016). Our results support the findings; HF patients with lower self-care scores were likely to be readmitted to the hospital.…”
Section: Discussionmentioning
confidence: 69%
“…Self‐care is considered the cornerstone of HF treatment and the prevention of rehospitalisation (Chamberlain, ; Navidian et al, ; Shao et al, ; Xie et al, ). Our results support the findings; HF patients with lower self‐care scores were likely to be readmitted to the hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies demonstrated that patients with poor symptoms recognition and self‐care behaviour have a high risk of subsequent hospitalizations . On the contrary, other showed greater risk of hospitalization associated with better self‐care, suggesting that more consistent engagement in self‐care behaviours is driven in part by the progressive nature of HF .…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies demonstrated that patients with poor symptoms recognition and self-care behaviour have a high risk of subsequent hospitalizations. 36,37 On the contrary, other showed greater risk of hospitalization associated with better self-care, suggesting that more consistent engagement in self-care behaviours is driven in part by the progressive nature of HF. 38 In fact, few studies have demonstrated a reduction in readmission rates based on HF self-care education even in a dyadic way, including the caregiver, 39,40 and the use of self-management programmes have also shown inconsistent effects on outcomes even if most of these studies enrolled patients younger than those enrolled in our cohort.…”
Section: Self-care Ability and Outcomesmentioning
confidence: 98%